EDUKASI TUGAS DAN FUNGSI OJK KEPADA MAHASISWA UNIVERSITAS MERANGIN - Riri Wulandari; Ade Taufan; Angra Melina; Hayati; Gion Rahmadan (AbdiMasya | Hira Institute, 2025)
This program aimed to educate Universitas Merangin students about the duties and functions of the Financial Services Authority (OJK). Using interactive lectures, group discussions, visual media, and consumer complaint simulations, the program provided both theoretical knowledge and practical experience. Evaluation through pre- and post-tests showed a significant increase in students’ understanding of OJK’s role in regulating, supervising, and protecting consumers in the financial services sector. Most participants expressed high satisfaction, indicating the program’s relevance and effectiveness in improving financial literacy.